2012
DOI: 10.1111/j.1748-720x.2012.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Bias in the Evaluation of Conflict of Interest Policies

Abstract: Physicians are affected by the conflict of interest (COI) policies they help formulate. This study examines whether physicians evaluate these policies impartially. One hundred and seventy‐nine physicians, 224 financial advisors, and 1,430 members of the general public evaluated the fairness and efficacy of a COI policy in either a medical or financial context. Physicians were more critical of the medical COI policy compared to a financial COI policy, while financial professionals displayed the reverse pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In turn, policy support depends partly on people’s judgments of their own and others’ likelihood of engaging in moral and immoral behaviors. Asymmetric self-righteousness predicts that people may be especially likely to resist policies aimed at preventing people’s own unethical behavior, simply because people do not believe they are likely to engage in immoral behaviors in the first place (Sharek, Schoen, & Loewenstein, 2012). In contrast, if people believe that they and others are equally likely to engage in ethical behavior, then policies that promote ethical behavior are less likely to be met with indifference or even resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, policy support depends partly on people’s judgments of their own and others’ likelihood of engaging in moral and immoral behaviors. Asymmetric self-righteousness predicts that people may be especially likely to resist policies aimed at preventing people’s own unethical behavior, simply because people do not believe they are likely to engage in immoral behaviors in the first place (Sharek, Schoen, & Loewenstein, 2012). In contrast, if people believe that they and others are equally likely to engage in ethical behavior, then policies that promote ethical behavior are less likely to be met with indifference or even resistance.…”
Section: Discussionmentioning
confidence: 99%
“…There is no guarantee that open declarations of COI will prevent such bias when researchers accept grant funding (whether or not it is restricted) from companies with vested interests in the outcomes generated. Further, a randomized study (Sharek, Schoen, & Loewenstein, 2012) Moreover, most scientists publish their studies in refereed journals, adding important, though imperfect (Dyer, 2019;John, Loewenstein, Marder, & Callaham, 2019), layers of protection against COI.…”
Section: Cois In Breastfeeding and Human Milk Researchmentioning
confidence: 99%
“…There is no guarantee that open declarations of COI will prevent such bias when researchers accept grant funding (whether or not it is restricted) from companies with vested interests in the outcomes generated. Further, a randomized study (Sharek, Schoen, & Loewenstein, 2012) showed that the impact of motivational bias may extend to the development and evaluation of COI policies when these policies are developed by those closest to the field. Involving impartial organizations and ethicists in the development of COI policies could help prevent this potential bias.…”
Section: Barriers and Challenges To Breastfeeding And Human Milk Resementioning
confidence: 99%
“…Most of these guidelines, however, are ambiguous and may not be applicable in managing chronic spinal pain utilizing contemporary IPM. Moreover, quality issues exist, including conflicts of interest and the inclusion or exclusion of significant literature of randomized trials and observational studies (101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116).…”
Section: Rationale and Importancementioning
confidence: 99%